Single and combined effect of bisphenol A with high sucrose diet on the diabetic and renal tubular dysfunction phenotypes in Drosophila melanogaster. - Rani, L.; Saini, S.; Thakur, R.S.; Patel, D.K.; Chowdhuri, D.K.; Gautam, N.K. (Environmental Toxicology and Pharmacology, 2022)
In the present study, effect of exposure of bisphenol A (BPA) and combined exposure of BPA + HSD has been investigated on the glucose homeostasis and associated renal complications in Drosophila. Exposure of 1.0 mM BPA alone induced type 2 diabetes like condition (T2D) in adult male D. melanogaster via oxidative stress. Elevated TGF-? signaling was evident by increased expression of baboon (babo) in BPA exposed organism that stimulated the modulation of extracellular matrix (ECM) component collagen IV resulting in the fibrosis of the Malpighian tubules (MTs). Combined exposure of BPA + HSD (high sucrose diet) resulted in the increased magnitude of T2D and MTs dysfunction parameters. Taken together, the study illustrates that BPA has diabetogenic potential in exposed Drosophila that caused adverse effects on their MTs and combined exposure with BPA and HSD could aggravate the renal tubular dysfunction. The study further suggests the use of Drosophila model to study the environmental chemicals induced diabetes mediated renal dysfunction.